Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ac301064g
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Detection of Single-Nucleotide Polymorphisms Using a Quartz Crystal Microbalance Biosensor Based on the Toehold-Mediated Strand Displacement Reaction

Abstract: Toehold-mediated strand displacement reaction (SDR) is first introduced to develop a simple quartz crystal microbalance (QCM) biosensor without an enzyme or label at normal temperature for highly selective and sensitive detection of single-nucleotide polymorphism (SNP) in the p53 tumor suppressor gene. A hairpin capture probe with an external toehold is designed and immobilized on the gold electrode surface of QCM. A successive SDR is initiated by the target sequence hybridization with the toehold domain and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 39 publications
(54 reference statements)
1
63
0
Order By: Relevance
“…The intensity decrease continued up to 60 min and no meaningful intensity change occurred afterward. This observation is analogous with those reported in previous publications [12,19] in which a double-strand was also pre-immobilized on a substrate surface before measurements; while, the displacement was completed approximately in 10 min when a double-strand was in a solution without immobilization on the surface [7,11,28]. The Raman spectrum acquired at 60 min of the displacement from the 200 pM sample (black) is also shown in Fig.…”
Section: Optimization Of Hybridization Location Of Idna and Displacemsupporting
confidence: 89%
See 1 more Smart Citation
“…The intensity decrease continued up to 60 min and no meaningful intensity change occurred afterward. This observation is analogous with those reported in previous publications [12,19] in which a double-strand was also pre-immobilized on a substrate surface before measurements; while, the displacement was completed approximately in 10 min when a double-strand was in a solution without immobilization on the surface [7,11,28]. The Raman spectrum acquired at 60 min of the displacement from the 200 pM sample (black) is also shown in Fig.…”
Section: Optimization Of Hybridization Location Of Idna and Displacemsupporting
confidence: 89%
“…Larkey et al [11] demonstrated a miRNA fluorescence sensor utilizing fluorescence quenching that occurs when two different dyes tagged at both ends of a freed reporter DNA became close by forming a hairpin structure (limit of detection (LOD): 10 nM). A quartz crystal microbalance (QCM)-based sensing scheme was also studied [12]. A hairpin capture probe became an open-loop structure by hybridization with a target DNA and then a streptavidin coupled reporter strand was allowed to bind on the opened probe for mass amplification (LOD: 0.3 nM).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques, including quartz-crystal microbalance [4], electrochemical [5], optic [6], and surface plasmon resonance [7] methods, have been widely studied for DNA detection. Among them, electrochemical biosensors have become very popular because of their great advantages, including simplicity, rapidity, portability, low cost, and high sensitivity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such detection limit is comparable to those reported methods coupled with complicated signal amplification means or even more sensitive than other common label-free approaches for microRNA detection (Table 1). In addition, the relative standard deviation (n ¼ 6) of the sensor for These comparisons indicate the high selectivity of the method, which is associated with the highly specific sequence-dependence of the TSDR [34].…”
Section: Resultsmentioning
confidence: 99%